Evaluation of adaptive capacity of slope regulation and storage measures on the Loess Plateau under drought stress - Siying Yan; Baisha Weng; Denghua Yan; Qiang Fu; Hao Wang (Agricultural Water Management)
The study evaluated the adaptive ability of slope regulation and storage measures (SRASM) under drought stress, providing scientific basis for improving water resource management and ecological protection in the arid environment of the Loess Plateau region. Four SRASM including afforestation on the hilltop (forestland engineering), returning farmland to forest on the hillside (grassland engineering), building terraces on the hillside (terraced fields engineering) and damming and silting on the valley floor (silting dam engineering) can effectively solve the problem of water and soil loss on the Loess Plateau. However, it is still unclear how the adaptive capacity (resistance and resilience) of these SRASM under drought stress. This study took the above four SRASM as the study object, used the performance of the four SRASM after drought and rehydration events as the basis for judging the adaptive capacity under drought stress. It proposed evaluation methods for drought and rehydration events, as well as calculation methods for resistance and resilience. Furthermore, it analyzed the adaptive capacity of different SRASM and different sub-basins in the middle reaches of the Yellow River under drought stress, as well as the impact of slope on adaptive capacity. The results showed that when light and moderate drought occurred, four SRASM recovered to their normal state after rehydration. In terms of resilience, forestland engineering > grassland engineering > terraced fields engineering > silting dam engineering, and grassland engineering had the most prominent ability to resist drought. As the slope increased, the adaptive capacity decreased. From a spatial perspective, the resilience in the western part of the middle reaches of the Yellow River was lower than that in the eastern, and the spatial distribution of resistance in the middle reaches of the Yellow River generally decreased from northwest to southeast.